Horizontal and vertical distribution of microplastics in Gehu Lake, China - Ruoying Yang; Xia Xu; Yingang Xue; Ling Zhang; Jun Guo; Liping Wang; Mingguo Peng; Qiuya Zhang; Yun Zhu (Water Supply, 2022)
Microplastics (MPs) widely exist in the aquatic environment. In this study, the horizontal and vertical distribution of MPs in different depths of Gehu Lake was analyzed. The study found that MPs were detected in water bodies at different depths. The Gehu Lake Basin's MP abundance throughout the entire lake region ranged from 1.40 to 5.53 n/L. Microplastic abundance in surface water (3.13 ± 0.32 n/L) was highest, and the average abundance of MPs in the middle water (2.28 ± 0.24 n/L) and bottom water (1.03 ± 0.14 n/L) was appreciably reduced (p < 0.05). The microplastics observed in water samples were analyzed, and it was found that the particle size of most of the obtained microplastic particles was between 100 and 500 microns, the main shape was fibrous MP, and the MP content of transparent color was highest, and the four most common MPs was polyethylene (PE), polystyrene, polyester (PES), and polypropylene (PP). In this article, we emphasize the importance of comprehending the specific distribution characteristics of MPs in Gehu Lake. It provides a data foundation for future monitoring of MPs present in Gehu Lake, provides scientific and technological support for the assessment and prevention of microplastic pollution in this area, and offers some assistance for future lake water quality regulation. HIGHLIGHTS It was investigated how microplastics were distributed both vertically and horizontally in Gehu Lake.; The influence of human factors on the distribution of microplastics was studied.; The distribution of microplastics in freshwater lakes in China was studied.; The particle size and color of microplastics in Gehu Lake was discovered.; A data basis is provided for future monitoring of microplastics in Gehu Lake water.;